Exploring the role of psychological well-being in the impact of hearing loss on depressive symptoms in rural older adults - Qi Sun; Zhaoquan Jiang; Zhaoxu Xu; Mingyue Zhou; Xiaoyan Zhang; Tao Liu; Shixue Zhou (Frontiers in Public Health)
ObjectiveExploring the Relationship between Hearing Loss, psychological well-being, and Depressive Symptoms in Rural older adults: Validating the Mediating Role of psychological well-being in the Impact of Hearing Loss on Depressive Symptoms to Provide a Theoretical Basis for Improving the Mental Health of Rural older adults.MethodsThe study focuses on 5,273 rural older individuals aged 65 and above, using data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) database. Hearing loss was assessed through self-report. Psychological well-being was evaluated using the Current Situation Assessment and Personality Emotional Characterization from the database. Depressive symptoms were measured using the short form of the Center for Epidemiologic Studies Depression Scale (CESD-10). The analysis involved using SPSS 27.0 and PROCESS v4.1 to conduct correlation analysis, regression analysis, and mediation effect analysis.ResultsThe depressive symptoms score for rural older individuals was (13.02 ± 4.48), and the psychological well-being score was (19.13 ± 2.47). There was a negative correlation between depressive symptoms and psychological well-being (r = −0.123, p < 0.001), there was a negative correlation between depressive symptoms and hearing loss (r = −0.086, p < 0.001). A negative correlation was also observed between hearing loss and psychological well-being (r = −0.060, p < 0.001). Psychological well-being mediates the effect of hearing loss on depressive symptoms among rural older individuals.ConclusionHearing loss in rural older individuals exerts both direct effects on depressive symptoms and indirect effects through the mediating role of psychological well-being. Specifically, the impairment of auditory function not only exacerbates emotional distress, but also diminishes psychological adaptability, thereby creating a dual pathway for depression development.